The efficacy and safety of indobufen in patients with ischemic cardiovascular or cerebrovascular diseases: systematic review and meta-analysis - Xiaolu Luo; Chenglu Lai; Tielong Chen (Frontiers in Cardiovascular Medicine)
ObjectiveThis meta-analysis aims to evaluate the safety and efficacy of indobufen in the treatment of cardiovascular diseases, cerebrovascular diseases, and thromboembolic disorders. The primary focus is on the incidence of major adverse cardiovascular events (MACE), thrombosis, bleeding events, and adverse reactions. The results are intended to provide a reference for the clinical application of indobufen and suggest directions for further large-scale, multi-center, prospective studies.MethodsThis review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library databases to identify all relevant studies on indobufen. Twelve trials, all randomized controlled trials (RCTs), met the inclusion criteria. The results were presented as risk ratios (RR) with 95% confidence intervals (CI), and meta-analysis was performed using RevMan 5.3 and Stata 18.0 software.ResultsThe meta-analysis included 12 randomized controlled trials. Regarding safety, indobufen showed superior clinical outcomes compared to other antiplatelet agents regarding bleeding events, gastrointestinal adverse reactions, and overall adverse reactions, with these differences being more pronounced in cardiovascular diseases. However, the effects of both treatments on efficacy outcomes, including MACE, myocardial infarction, angina, mortality, and thrombotic events, were similar. For stroke events, particularly in patients with cerebrovascular diseases, the use of indobufen was associated with some risk.ConclusionIndobufen is associated with a lower risk of adverse reactions and bleeding, making it a viable option for patients at risk of bleeding or adverse effects, particularly in those with cardiovascular diseases. However, compared to anticoagulants such as aspirin and clopidogrel, indobufen has a shorter history of use, and its evidence base is relatively limited, highlighting the need for further research. Currently, indobufen is widely used in secondary cardiovascular and cerebrovascular prevention and provides some guidance for antiplatelet therapy in patients with gastrointestinal discomfort or bleeding risk. However, due to the potential risks in MACE, stroke, and other events, further clinical trials are needed to assess the clinical applicability of indobufen.Systematic Review Registrationhttps://www.crd.york.ac.uk/, identifier (CRD42024587938).